2021
DOI: 10.1002/art.41548
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Control of Articular Cartilage and Subchondral Bone Homeostasis in Mice Requires Osteocytic Transforming Growth Factor β Signaling

Abstract: Objective. Transforming growth factor β (TGFβ) signaling plays a complex tissue-specific and nonlinear role in osteoarthritis (OA). This study was conducted to determine the osteocytic contributions of TGFβ signaling to OA. Methods. To identify the role of osteocytic TGFβ signaling in joint homeostasis, we used 16-week-old male mice (n = 9-11 per group) and female mice (n = 7-11 per group) with an osteocyte-intrinsic ablation of TGFβ receptor type II (TβRII ocy−/− mice) and assessed defects in cartilage degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…These differences in shape and orientation of the osteocyte lacune between the regions are possibly indicators of the transition process from woven to lamellar bone [24]. In addition, these results are also suggestive of dynamic active perilacunar remodelling in CA- regions, which has been reported to be a direct consequence of local osteocyte-derived TGFβ signalling [7, 12, 31-33]. Further, quantitative histological assessment (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These differences in shape and orientation of the osteocyte lacune between the regions are possibly indicators of the transition process from woven to lamellar bone [24]. In addition, these results are also suggestive of dynamic active perilacunar remodelling in CA- regions, which has been reported to be a direct consequence of local osteocyte-derived TGFβ signalling [7, 12, 31-33]. Further, quantitative histological assessment (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Evidence also supports osteocytes as the most important mechano-responsive cells in bone [45], with the greatest potential to link mechanical overloading in OA to a cellular response. Interesting also, is a report that mechanosensation of subchondral bone require osteocytic TGFβ1 signalling [33] and that compressive stress changed the effect of TGFβ1 on RANKL and OPG expression in cement-oblasts and osteoblasts [46].…”
Section: Discussionmentioning
confidence: 99%
“…Mazur et al 36 reported that osteocytic matrix metalloproteinase 13 (MMP13) deficiency exerts a protective effect on early OA, via its effects on PLR. Bailey et al 37 verified that subchondral bone remodelling in response to injury requires osteocytic TGF-β signalling. Thus, our pioneering efforts, which obtained evidence by applying accepted concepts related to bone research and OA investigations, may reveal osteocyte-related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…( Peng et al, 2021 ). The unique structure and composition of the cartilage ECM are important factors in maintaining cartilage homeostasis, providing a smooth joint articulation and enabling articular cartilage to withstand loads several times the body weight ( Bailey et al, 2021 ; Peng et al, 2021 ). COL2 is the most abundant component in the ECM of cartilage, where it forms a fibrous network structure; while GAG absorbs a large amount of water to form gel, and thus maintaining the dilatability and elasticity of cartilage ( Sherwood et al, 2014 ).…”
Section: Cartilage Homeostasismentioning
confidence: 99%